Cytotoxicity of snake venom Lys49 PLA2-like myotoxin on rat cardiomyocytes ex vivo does not involve a direct action on the contractile apparatus - López Dávila, Alfredo Jesús (2021)
Viperid snake venoms contain a unique family of cytotoxic proteins, the Lys49 PLA2 homologs, which are devoid of enzymatic activity but disrupt the integrity of cell membranes. They are known to induce skeletal muscle damage and are therefore named ‘myotoxins’. Single intact and skinned (devoid of membranes and cytoplasm but with intact sarcomeric proteins) rat cardiomyocytes were used to analyze the cytotoxic action of a myotoxin, from the venom of Bothrops asper. The toxin induced rapid hypercontraction of intact cardiomyocytes, associated with an increase in the cytosolic concentration of calcium and with cell membrane disruption. Hypercontraction of intact cardiomyocytes was abrogated by the myosin inhibitor para-aminoblebbistatin (AmBleb). No toxin-induced changes of key parameters of force development were observed in skinned cardiomyocytes. Thus, although myosin is a key effector of the observed hypercontraction, a direct effect of the toxin on the sarcomeric proteins -including the actomyosin complex- is not part of the mechanism of cytotoxicity. Owing to the sensitivity of intact cardiomyocytes to the cytotoxic action of myotoxin, this ex vivo model is a valuable tool to explore in further detail the mechanism of action of this group of snake venom toxins.